Working forests in the neotropics : conservation through sustainable management? - Zarin, Daniel (Biology and resource management in the tropics series, 2004)
Neotropical forests sustain a wealth of biodiversity, provide a wide range of ecosystem services and products, and support the livelihoods of millions of people. But is forest management a viable conservation strategy in the tropics? Supporters of sustainable forest management have promoted it as a solution to problems of both biodiversity protection and economic stagnation. Detractors insist that any conservation strategy short of fully protected status is a waste of resources and that forest management actually hastens deforestation. By focusing on a set of critical issues and case studies, this book explores the territory between these positions, highlighting the major factors that contribute to or detract from the chances of achieving forest conservation through sustainable management.
Keywords: Forests and forestry : Latin America; Forest conservation : Latin America; Forest management : Latin America; Sustainable forestry : Latin America